The Role and Symbolic Meaning of the Wacan Syekh Oral Tradition in Fostering Community Social Culture - Bahrudin, Memet Isa; Qomaruzzaman, Bambang; Albustomi, Ahmad Gibson (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2026)
This study investigates the preservation of Wacan Syekh, an oral tradition (also called Reading or Wawacan Layang of Sheikh Abdul Qodir Jaelani) in Renged Village, Tangerang Regency, Banten, as intangible cultural heritage blending religion, local culture, and social values. Employing a qualitative descriptive-interpretive approach grounded in phenomenology and symbolic interactionism/social constructivism, it analyzes data from participatory observation, interviews, and documentation via Miles and Huberman's model. Findings reveal Wacan Syekh's role as a medium for moral-spiritual learning, community solidarity, and noble value internalization through symbols like water and seven-colored flowers, functioning as spiritual protection and cultural identity preserver relevant to national character development.